Feasibility of infant cord blood HIV testing for anti-retroviral post-exposure prophylaxis - Irene W. Inwani; Ruth W. Nduati; Rachel M. Musoke (Journal of Infection in Developing Countries)
Background: Many maternity hospitals in developing country settings deliver women who are of unknown HIV status. The main objectives of this study were to evaluate the acceptability of post-partum infant cord blood HIV testing and the subsequent uptake of interventions to prevent mother-to-child transmission of HIV. Methodology: This was a cross-sectional study among infants delivered to women of unknown HIV status at the maternity ward of the Kenyatta National hospital, Kenya. At the time of delivery, five milliliters of cord blood was collected from consecutive singleton-birth infants born to women with unknown HIV status. After delivery, the women were counseled and consent was sought for HIV antibody testing of the cord blood. Anti-retroviral post-exposure prophylaxis was provided for HIV exposed infants and their mothers counseled on infant feeding. Results: Overall 220 (87%) of the 253 mothers gave consent for HIV testing. This included 35 (90%) of 40 mothers of babies with HIV positive cord blood and 184 (86.4%) of 213 with HIV negative cord blood. Seventeen (48.6%) of the 35 women who knew their status accepted to administer anti-retroviral prophylaxis to their infants, and 28 (80%) chose to breast-feed their infants. Conclusions: Infant cord blood testing is highly acceptable among women who deliver with an unknown HIV status and provides an additional entry point for prevention of mother-to-child transmission of HIV.